Restorasi dan Konservasi berbasis Komunitas: Meningkatkan Kesejahteraan Masyarakat melalui Program Katingan Mentaya Project Kalimantan: Restorasi dan Konservasi berbasis Komunitas: Meningkatkan Kesejahteraan Masyarakat melalui Program Katingan Mentaya Project Kalimantan - Rahadyan, Rahadyan; Ardiyantika, Sulistyary (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2024)
This study explores the business concepts implemented by PT. Rimba Makmur Utama (PT. RMU) within its operational units, focuses on the Katingan Mentaya Project aimed at community-based conservation. The research employs descriptive statistical approaches alongside quantitative and qualitative methods to evaluate the implementation of five principles of community-based conservation by RMU. Findings indicate that RMU has successfully established collaborative relationships with the community through partnerships and the use of the CADASTA platform. Additionally, women are identified as key agents of change through active participation in floating health posts, rattan craft training, and microfinance skill development. Mediation and compensation are implemented through activities such as Zero Burn Zero Chemical (TBTK), Agroecology Farmer School (STA), and local plant conservation initiatives. A rights-based approach is reflected in RMU's efforts to improve community sanitation infrastructure. The revitalization of traditional and local institutions is also prioritized to maintain traditional knowledge in environmental management, exemplified by the Agroecology Sustainable Farmer Cooperative and the Peatland Sustainable Farmer Group in Bamadu Village. This study illustrates RMU's contribution to introducing innovation in conservation while strengthening community participation and cultural revitalization to achieve sustainable and inclusive environmental management.